Health Care Financing In Iran; Is Privatization A Good Solution? - T Walley; A Haycox; M Davari (Tehran University of Medical Sciences, 2012)
Background: This paper considers a range of issues related to the financing of health care system and relevant government policies in Iran.Methods: This study used mixed methods. A systematic literature review was undertaken to identify relevant publications. This was supplemented by hand searching in books and journals, including government publications. The issues and uncertainties identified in the literature were explored in detail through semi-structured interviews with key informants. These were triangulated with empirical evidence in the form of the literature, government statistics and independent expert opinions to validate the views expressed in the interviews.Results: The systematic review of published literature showed that no previous publication has addressed issues relating to the financing of healthcare services in Iran. However, a range of opinion pieces outlined issues to be explored further in the interviews. Such issues summarised into four main categories.Conclusion: The health care market in Iran has faced a period in which financial issues have enhanced managerial complexity. Privatization of health care services would appear to be a step too far in assisting the system to confront its challenges at the current time. The most important step toward solving such challenges is to focus on a feasible, relevant and comprehensive policy, which optimises the use of health care resources in Iran.